Peculiarities of Correlation of Personality’s Emotional Maturity and Professional Tolerance - Kandyba, Maria (Psychological Prospects Journal, 2015)
The paper considers the problem of emotional maturity of personality and its development, which appears in various works of both domestic and foreign specialists that analyse fields of professional activity. It traces the relationship between stage of professional development, formation of professional identity tolerance and components of emotional maturity.The research carried out within the framework of the article, allowed us to estimate the emotional maturity of the following criteria: expressiveness (EX) – displayed of emotions in facial expressions, transformation actions (EIX), the ability to convey the mood of surrounding (EEK); self-regulation (S) – the ability to manage their emotions, to deter unwanted and produce the desired, so as adjusting own behavior (Ae), and the behavior of others (BO); empathy (EM) – the ability to understand the emotional state of others (IEM), and appropriately use these skills in interacting with people (IEM).It is indicated, that tolerance in modern education is included in the set of goals in system of education, serving as a personal quality,  contributing to self-learning  and self-education aimed at developing of the professional knowledge, skills and tolarant attitude towards others. The main way to achieve quality of Ukrainian professional education in the international market is associated with attempts to modernize the entire higher education system, its structure, academic services.The analysis of the emotional maturity indicates the absence of differentiated indices of human emotional maturity achievement. The most successful example of such research is to study the  correlation of professional identity and tolerance.It is revealed that professional tolarance is the main factor of individual emotional maturaty. In addition, the study of emotional maturity indices in the  context of professional tolarance development is urgent for applied psychology.